Should the preservation of residual renal function cost volume overload and its consequence left ventricular hypertrophy in new hemodialysis patients? - Gunal, AI; Kirciman, E; Guler, M; Yavuzkir, M; Celiker, H (Marcel Dekker Inc, 2004)
Background. Left ventricular hypertrophy (LVH) is an important predictor of mortality in dialysis patients. The loss of residual renal function (RRF) appears to occur more rapidly in hemodialysis than continuous ambulatory peritoneal dialysis (CAPD). It is more likely that volume expansion in patients on CAPD may preserve RRF. The aim of this study was to investigate whether there is a cause-effect relationship between volume overload and preserving RRF in new hemodialysis patients. Methods. Nineteen patients with end-stage renal disease (ESRD) starting hemodialysis therapy were included in the study. At the beginning, their elevated blood pressures (BP) were treated with antihypertensive drugs. Thereafter, until normovolemia and normal BP were obtained, strict volume control was applied. The effects of both treatment modalities on the loss of RRF and LVH were evaluated prospectively. Results. At the initial examination, all of the patients were hypertensive and had markedly increased left ventricular mass index (LVMI). The daily urine production was 1575+/-281 mL. At the end of drug treatment period lasting three months, although BP significantly decreased, daily urine production and LVMI only decreased by 12% and 6%, respectively. At the end of the period in which strict volume control was applied, the body weight significantly decreased (from 60+/-5 to 55+/-8 kg, p<0.0001). This decrease in body weight was accompanied by marked decreases in dilated cardiac chamber size and more importantly daily urine production. At the end of this period, while 7 of 19 patients had no residual urine production, residual urine production was below 200 mL/d in the remaining 12 patients. Although the period of volume control was short, there was significant reduction in the LVMI (decreased from 251+/-59 to 161+/-25 gr/m(2), P<0.0001). Conclusion. The results of our prospective study have clearly shown that the persistence of residual renal function in patients with ESRD starting hemodialysis therapy may largely depend on volume overload. Equally interesting was the finding that despite significantly reduced BP level with hypotensive drugs, there was no marked regression in LVMI. In the contrary, after the volume control period, LVMI was significantly decreased. Our results support the hypotheses that decrease in volume may be more important than pressure reduction in regressing the left ventricular hypertrophy.
Keywords: RRF; LVH; hypertension; strict volume control; antihypertensive drug; hemodialysis